The Effects of Exergaming on Executive and Physical Functions in Older Adults With Dementia: Randomized Controlled Trial - Shanshan Wu; Hongqing Ji; Junyeon Won; Eun-Ah Jo; Yun-Sik Kim; Jung-Jun Park (JMIR Publications, 2023)
BackgroundDespite increasing interest in the effects of exergaming on cognitive function, little is known about its effects on older adults with dementia. ObjectiveThe purpose of this is to investigate the effects of exergaming on executive and physical functions in older adults with dementia compared to regular aerobic exercise. MethodsIn total, 24 older adults with moderate dementia participated in the study. Participants were randomized into either the exergame group (EXG, n=13, 54%) or the aerobic exercise group (AEG, n=11, 46%). For 12 weeks, EXG engaged in a running-based exergame and AEG performed a cycling exercise. At baseline and postintervention, participants underwent the Ericksen flanker test (accuracy % and response time [RT]) while recording event-related potentials (ERPs) that included the N2 and P3b potentials. Participants also underwent the senior fitness test (SFT) and the body composition test pre- and postintervention. Repeated-measures ANOVA was performed to assess the effects of time (pre- vs postintervention), group (EXG vs AEG), and group×time interactions. ResultsCompared to AEG, EXG demonstrated greater improvements in the SFT (F1.22=7.434, P=.01), reduction in body fat (F1.22=6.476, P=.02), and increase in skeletal mass (F1.22=4.525, P=.05), fat-free mass (F1.22=6.103, P=.02), and muscle mass (F1.22=6.636, P=.02). Although there was a significantly shorter RT in EXG postintervention (congruent P=.03, 95% CI 13.581-260.419, incongruent P=.04, 95% CI 14.621-408.917), no changes occurred in AEG. EXG also yielded a shorter N2 latency for central (Cz) cortices during both congruent conditions compared to AEG (F1.22=4.281, P=.05). Lastly, EXG presented a significantly increased P3b amplitude compared to AEG during the Ericksen flanker test (congruent: frontal [Fz] F1.22=6.546, P=.02; Cz F1.22=5.963, P=.23; parietal [Pz] F1.22=4.302, P=.05; incongruent: Fz F1.22=8.302, P=.01; Cz F1.22=15.199, P=.001; Pz F1.22=13.774, P=.001). ConclusionsOur results suggest that exergaming may be associated with greater improvements in brain neuronal activity and enhanced executive function task performance than regular aerobic exercise. Exergaming characterized by both aerobic exercise and cognitive stimulation can be used as an effective intervention to improve cognitive and physical functions in older adults with dementia. Trial RegistrationClinical Research Information Service KCT0008238; https://cris.nih.go.kr/cris/search/detailSearch.do/24170